2020
DOI: 10.1021/acsomega.0c01603
|View full text |Cite
|
Sign up to set email alerts
|

Homeotropically Aligned Monodomain-like Smectic-A Structure in Liquid Crystalline Epoxy Films: Analysis of the Local Ordering Structure by Microbeam Small-Angle X-ray Scattering

Abstract: For the development of functional thin films with high thermal conductivity, the local ordering structure of a cured liquid crystalline epoxy resin (LCER) droplet was investigated by using synchrotron radiation microbeam small-angle X-ray scattering. The cured LCER in the vicinity of a substrate with low surface free energy was revealed to form a polydomain smectic-A (SmA) structure in which the normal direction of the layers was random in each domain, although the alignment was planar near the air interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Hence, the thermal conductivity of pure thermosetting resins for preparing a polymer composite can be considered valuable if it can secure a thermal conductivity of 1–2 W/m·K. , Particularly, regarding epoxy resins (ERs), which consist of tricyclic LC epoxy, phenol resin, and triphenylphosphine, their maximum reported isotropic thermal conductivity value is 1.16 W/m·K . Additionally, the same research group revealed that the same epoxy achieved up to 5.8 W/m·K conductivity after a surface treatment in an amine curing system, although the value was the anisotropic maximum . These studies were greatly significant because they represent a breakthrough for the limits of organic matter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the thermal conductivity of pure thermosetting resins for preparing a polymer composite can be considered valuable if it can secure a thermal conductivity of 1–2 W/m·K. , Particularly, regarding epoxy resins (ERs), which consist of tricyclic LC epoxy, phenol resin, and triphenylphosphine, their maximum reported isotropic thermal conductivity value is 1.16 W/m·K . Additionally, the same research group revealed that the same epoxy achieved up to 5.8 W/m·K conductivity after a surface treatment in an amine curing system, although the value was the anisotropic maximum . These studies were greatly significant because they represent a breakthrough for the limits of organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were greatly significant because they represent a breakthrough for the limits of organic matter. However, the global utilization of the materials was limited by the high conductivity values obtained by the film, as well as the fact that most of them required special processing. , To the best of our knowledge, the maximum thermal conductivity of epoxy bulk systems, which could be utilized globally, must be <0.5 W/m·K; those with relatively high values are LC materials. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TM/DAN on G1 had not been prepared in this study because GISAXS measurements of it had already been reported in our previous paper. 18,19 3. RESULTS AND DISCUSSION 3.1.…”
Section: Surface Treatments and Estimation Of Surfacementioning
confidence: 99%
“…Previous studies 34,42 found that LC epoxy resins spontaneously form planar or homeotropic alignments depending on the surface free energy of the substrates on which the LC epoxy monomer is polymerized. Specifically, the cured product obtained from the LC epoxy monomer was revealed to form a homeotropically aligned smectic A structure on a substrate possessing a relatively high surface free energy (73 mN/m), and the cross-linked LC epoxy resin showed a maximum thermal conductivity of 5.8 W m À1 K À1 in the molecular chain direction.…”
Section: Introductionmentioning
confidence: 99%